Visualization of the amygdalo–hippocampal border and its structural variability by 7T and 3T magnetic resonance imaging. Issue 9 (12th March 2014) - Derix, Johanna; Yang, Shan; Lüsebrink, Falk; Fiederer, Lukas Dominique Josef; Schulze‐Bonhage, Andreas; Aertsen, Ad; Speck, Oliver; Ball, Tonio
Abstract The amygdala and the hippocampus are two adjacent structures in the medial temporal lobe that have been broadly investigated in functional and structural neuroimaging due to their central importance in sensory perception, emotion, and memory. Exact demarcation of the amygdalo‐hippocampal border (AHB) is, however, difficult in conventional structural imaging. Recent evidence suggests that, due to this difficulty, functional activation sites with high probability of being located in the hippocampus may erroneously be assigned to the amygdala, and vice versa. In the present study, we investigated the potential of ultra‐high‐field magnetic resonance imaging (MRI) in single sessions for detecting the AHB in humans. We show for the first time the detailed structure of the AHB as it can be visualized in T1‐weighted 7T in vivo images at 0.5‐mm3 isotropic resolution. Compared to data acquired at 3T, 7T images revealed considerably more structural detail in the AHB region. Thus, we observed a striking inter‐hemispheric and interindividual variability of the exact anatomical configuration of the AHB that points to the necessity of individual imaging of the AHB as a prerequisite for accurate anatomical assignment in this region. The findings of the present study demonstrate the usefulness of ultra‐high‐field structural MRI to resolve anatomical ambiguities of the human AHB. Highly accurate morphometric and functional investigations in this region at 7T may allow addressing such hitherto unexplored issues as whether the structural configuration of the AHB is related to functional differences in amygdalo‐hippocampal interaction. Hum Brain Mapp 35:4316–4329, 2014. © 2014 Wiley Periodicals, Inc.